(untitled) (Fiep Bulletin - online, 2014)
Students attending bodybuilding academies which form common sense, that exercise performed at low speed enforcement induces greater muscle damage. The aim of this study was to monitor the behavior of strength, power and thigh circumference in males before and after a protocol rated speed fast and slow movements execution concentric- eccentric. Sample consisted of 10 healthy male, practitioners of the volleyball. Divided into two groups, the first of which, 5 subjects (+0.71 = 16.50 years), called Fast Speed ??Group (GVR), performed mechanical actions with time to 1.5 seconds each repetition. Second group was of 5 individuals (+0.58 = 16.67 years), called Group Slow Speed ??(GVL), which held such shares at 6 seconds per repetition. The tests used were: 1RM (leg press and leg extension 90), thigh circumference (PC), standing long jump (SHP), total body mass and stature. The tests were performed the day before and 5 days following the completion of the intervention. At the end of this research, noted that the training protocol with fast speed generated higher percentage declines in tests of 1RM in the leg press (0hours = 24.41%; 24hours = 28.35%; 48hours = 15.75%, 72hours = - 11.81% and 96hours =-32.28) in knee extension (0hours = 32.68 %; 24hours = 31.71%; 48hours = 24.39%, -10.73% and = 72hours = -31 96hours, 71%), SHP (0horas = 12.54%; 24hours = 11.53%, 13.45% = 48 hours, 72 hours and 96 hours = -6.47% = -8.39%) and increase in PC (0horas = 2.90%, 3.02% = 24 hours , 48hours = 2.82%, 72hours = 96hours = -0.59 and -0.82). This study the training GVR generated higher muscle damage, thus increasing the PC and income fall in 1RM test and SHP, compared to the group that conducted the training protocol with GVL .